2013
DOI: 10.1021/jp404287t
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Property Weighted Radial Distribution Functions Descriptors of Metal–Organic Frameworks for the Prediction of Gas Uptake Capacity

Abstract: Metal–organic frameworks (MOFs) are porous materials with exceptional host–guest properties with huge potential for gas separation. The combinatorial design of MOFs demands the in silico screening of the nearly infinite combinations of structural building blocks using efficient computational tools. We report here a novel atomic property weighted radial distribution function (AP-RDF) descriptor tailored for large-scale Quantitative Structure–Property Relationship (QSPR) predictions of gas adsorption of MOFs. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
170
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(172 citation statements)
references
References 48 publications
(74 reference statements)
1
170
1
Order By: Relevance
“…In real space, a pair of 'weighted RDFs' ξ 2 (r) and ξ 1 (r) can be used (a related idea occurs in the use of 'RDF descriptors' for chemical structure 38,39 ). The first shows up fractionation irrespective of how the phases differ, but does not show the direction of fractionation.…”
Section: Discussionmentioning
confidence: 99%
“…In real space, a pair of 'weighted RDFs' ξ 2 (r) and ξ 1 (r) can be used (a related idea occurs in the use of 'RDF descriptors' for chemical structure 38,39 ). The first shows up fractionation irrespective of how the phases differ, but does not show the direction of fractionation.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several recent studies dedicated to answering this question using models developed by machine learning 32,45,114,[131][132][133][134] , a field that is becoming extremely powerful in materials science 135,136 . It was shown that 1-dimensional geometric descriptors are able to successfully predict adsorption at high pressures 134,137 and low temperatures 114 , using representative datasets of materials to train machine learning models. These models are however, rather poor at predicting performance at lower gas densities, in pressure regions of 0 -1 bar 134 .…”
Section: H1 Data Mining Approachesmentioning
confidence: 99%
“…It was shown that 1-dimensional geometric descriptors are able to successfully predict adsorption at high pressures 134,137 and low temperatures 114 , using representative datasets of materials to train machine learning models. These models are however, rather poor at predicting performance at lower gas densities, in pressure regions of 0 -1 bar 134 . This is likely due to the oversimplified nature of these descriptors, when a more detailed representation of the chemistry and pore shape is needed.…”
Section: H1 Data Mining Approachesmentioning
confidence: 99%
See 2 more Smart Citations